Physicomechanical and Thermal Properties of Particle Board Produced Using Waste Ceramic Materials and Corncob - O. J. Aladegboye; O. J. Oyedepo; T. J. Awolola; O. D. Oguntayo; O. Y. Babatunde; O. T. Ilesanmi; P. P. Ikubanni (Advances in Materials Science and Engineering)
Waste management and recycling have led to numerous studies on particleboard production. This study attempted to use milled corncob (MCC) and waste ceramic tiles (WCTs) to produce particleboard. The MCC (100−70 wt.%) and WCT (0–30 wt.%) were mixed at different ratios, mixed and compressed at a pressure of 0.25 MPa using urea formaldehyde (UF) resin as adhesive. The physicomechanical and thermal properties of the particleboards produced were investigated. The physical properties (bulk density, water absorption, and thickness swelling) improved with composite particleboard compared to the 100% MCC particleboard. The increase in WCT yielded improved density and lowered the particleboard’s water absorption and thickness swelling. The mechanical tests showed that MOE values were below the recommended standard, which makes them unsuitable for structural use. However, MOR revealed values above the recommended standard. The thermal conductivity of the particleboards was reduced with increased WCT, and the required standard was found to be met. Hence, the particleboards produced are found helpful as thermal wall insulators. Based on the experiments done, sample R7 (70% MCC and 30% WCT) was considered the most preferable since it achieved the most preferable physicomechanical and thermal conductivity performance. The particleboards produced are recommended for wall partitioning and other internal and external purposes.